Analysis of Relationships Between Distribution of Population and Spatial Economy of Communes in the Kraków Metropolitan Area - Gorczyca, Katarzyna (Bulletin of Geography. Socio-economic Series, 2008)
The expansion of developed areas is one the factors that influence the distribution of population. Spatial policy implemented by communes reflects the existing tendencies but is also a factor that moulds the occurring processes. The aim of this article is to present the planned development of areas designated for investing, depending on the existing density of population. The article presents relationships between location and present distribution of population, and planned degree of expansion of development of communes located within the Kraków Metropolitan Area (the "KMA"). The range of areas designated for investing was analysed based on valid commune planning documents, which means that the article took into account 52 land use plans concerning all the communes that form the Kraków Metropolitan Area. The object of analysis is the spatial policy of communes related to the expansion of development, as well as demographic conditions of the Kraków Metropolitan Area.